From Reality to Virtuality: Digital Transformation on Luxury Brand Engagement and Purchase Intention in the Metaverse. - Mudava, Iasmina (2025)
Currently, luxury brands face the complexity of the concept of luxury and the constant evolution of consumers, making effective digital presence and communication essential. Interaction in digital channels strongly influences purchase decisions, requiring continuous monitoring by organizations. With the growing interest in the Metaverse, luxury brands are exploring new integration strategies in this digital universe. Based on the theory of digital transformation and the theory of consumer engagement, this study aims to analyze how Metaverse integration strategies shape the digital transformation of luxury brands and influence the engagement of luxury consumers in the digital realm. A mixed-methods approach was used, combining a qualitative approach through exploratory research and a quantitative approach through an online questionnaire (Study 1: n = 248, and Study 2: n = 198) disseminated in Prolific platform, where specific consumer habits (e.g., luxury products buying) are considered as filters to better select the targeted sample. The results revealed that Metaverse integration and digital transformation strategies positively impact purchase intention, but consumer engagement does not significantly moderate these relationships. This study highlights the importance of digital strategies adopted for the success of luxury brands in the Metaverse and suggests future research on the factors that affect the effectiveness of engagement in the Metaverse environment. DOI: https://doi.org/10.54663/2182-9306.2024.SpecialIssueMBP.92-139